Reverso : revista de estudios lesbianos, gays, bisexuales, transexuales, transgénero…. (Madrid : Higueras Arte, 2000)
Fonds Suzan Daniel (FSD)
Periodiciteit : viermaandelijks
Redactie : Aguila Real 24, Molina de la Hoz, 28230 Madrid
Spaans
Periodiek